Thursday

April 24, 2014

April 24, 2014

Posted by **Dee** on Wednesday, January 5, 2011 at 10:08pm.

(sq.root of 3 + 1)(sq.root of 3 - 1) in simplest form?

- Math -
**Reiny**, Wednesday, January 5, 2011 at 10:43pm(√3 + 1)(√3 - 1)

= 3 - 1

= 2

this has the pattern of the difference of squares just like

(a+b)(a-b) = a^2 - b2

**Related Questions**

Algebra - I had to solve 2x^2-x-1 using the quad. formula. I got it down to (1...

Calculus I - Find the derivative ** (sq root) y = (square root) x + (2nd sq root...

Algebra - I had to solve the function g of f where f is x^2+1 and g is sq. root ...

Trigonometry - I'm trying to find the cosecant of 11 pi/6. The answer is -2, but...

Algebra - Can you explain how to find the solution of 3x^2-2x+5, using the ...

Math - 1) Solve equation 3r+5 _____ + 2 = 2r to find the value of r? 2 A. 2 1/7 ...

math - simplify square 48/square6 square root(48) is the same as sq root (8) x ...

Math - Which of these is an irrational number? A.. Sq root of 14 B. -sq root of ...

Trig. - Can you please review this to see if I did this right? 2cos^2x+3cosx=0 ...

Trig. - 2sin^2x-3sinx=-1 sin^2x-3sinx=-1/2 times -3 sq. root of (sin^2x)+sinx= ...